2021
DOI: 10.1128/aem.01371-21
|View full text |Cite
|
Sign up to set email alerts
|

Higher Concentrations of Bacterial Enveloped Virus Phi6 Can Protect the Virus from Environmental Decay

Abstract: Phage Phi6 is an enveloped virus considered as a possible non-pathogenic surrogate for SARS-CoV-2 and other viral pathogens in transmission studies. Higher input amounts of bacteriophage Phi6 are shown to delay and protect the phage from environmental decay, both when the phage are dried in plastic tubes, and when they are stored in saline solution at 4°C. By contrast, when bacteriophage Phi6 are placed in LB (Luria-Bertani) growth medium (instead of saline) prior to placement on the plastic surface, the influ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…The impact of inoculum level on virus persistence on fomites has been highlighted previously ( 15 17 , 19 ). Lai et al ( 19 ) observed greater survival of SARS-CoV-1 at higher virus titers (4, 5, and 6 log 50% tissue culture infective dose [TCID 50 ]/mL) with survival times ranging from <5 min to 48 h following inoculation on paper, a disposable gown, and a cotton gown.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…The impact of inoculum level on virus persistence on fomites has been highlighted previously ( 15 17 , 19 ). Lai et al ( 19 ) observed greater survival of SARS-CoV-1 at higher virus titers (4, 5, and 6 log 50% tissue culture infective dose [TCID 50 ]/mL) with survival times ranging from <5 min to 48 h following inoculation on paper, a disposable gown, and a cotton gown.…”
Section: Resultsmentioning
confidence: 64%
“…Lai et al ( 19 ) observed greater survival of SARS-CoV-1 at higher virus titers (4, 5, and 6 log 50% tissue culture infective dose [TCID 50 ]/mL) with survival times ranging from <5 min to 48 h following inoculation on paper, a disposable gown, and a cotton gown. Bangiyev et al ( 17 ) observed longer half-lives (overall range of 5 to 57 min) of Φ6 in a saline inoculum matrix when vacuum-dried on plastic tubes at approximately 4 log PFU versus when evaluated at lower concentrations (3 and 2 log PFU). However, longer half-lives at increased inoculation levels were not observed with Φ6 in a Luria-Bertani inoculum matrix on plastic (half-lives ranged from 9 to 18 h), which provides evidence that extended survival may not always result from an increased inoculum titer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations